PP12 Functional Applications and Bioactive Compounds of Quinoa.(Chenopodium quinoa Willd.): Bibliometric Analysis and Systematic Review - Eduardo Palomino, Karina Erika; Saldaña Villa, Erick Manuel (Revista Productos Naturales, 2025)
Quinoa (Chenopodium quinoa Willd.) is a pseudocereal native to the Andes with an outstanding nutritional profile [1,2], including high quality proteins, essential amino acids, vitamins, minerals and bioactive compounds such as flavonoids and saponins [3] . Due to these properties, scientific research has grown in recent years. This study aimed to perform a bibliometric and systematic review of the scientific literature on the bioactive compounds, nutritional value and applications of quinoa, published between 2019 and 2025.